Physico-chemical analysis of selected ground water samples of Agra city, India - Yadav, Krishna Kumar; Gupta, Neha; Kumar, Vinit; Arya, Sandeep; Singh, Deepak (Recent Research in Science and Technology, 2013)
The aim of present study was carried out to assess the status of the groundwater in Agra city .The range of physicochemical parameters like pH (7.2-7.7), EC (1580-5200 mmhos), TDS (1020-4950 mg/l), Turbidity (1.1-31.4 NTU), Total Alkalinity (330-525 mg/l), Total hardness 240-1425 mg/l), Chloride (295-1140 mg/l), Calcium (72-436 mg/l), Magnesium 14.6-151.2 mg/l), Sodium (126.5-1254.9 mg/l) and Potassium (1.9-60.6 mg/l) were found to be higher than the natural background level of groundwater. This indicates the groundwater pollution in selected water samples from 12 sampling sites from Feb. to May 2011 of Agra city. The results considered that the groundwater of the study area in general cannot be considered as good quality.